Element of Loss in Qualifying an Act as an Unlawful Act - Muhammad Hafizhan Armansyah; Adlin Budhiawan (Warmadewa Press, 2024)
The aim of this research is to determine the criteria for classifying losses as aspects of criminal acts and the factors judges take into account when classifying losses. This study employs a normative research methodology, which is legal research that views the law as a set of norms. The data sources used in this study are secondary sources, namely journals, Supreme Court Decisions RI Number 2638 K/Pdt/2014, and some laws. Research Results According to R. WirjonoProjodikoro: R. Wirjono Projodikoro interprets the word onrechtmatigedaad as an unlawful act. According to him, the word